BIBLIOTERAPI DALAM MENINGKATKAN MOTIVASI BELAJAR REMAJA DI TAMAN BACA MASYARAKAT - Hairunnisa BR Sagala (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2018)
Seeing the current phenomenon that is very easily contaminated with the flow of technology that is so fast, making teenage turmoil toward negative things that lead to poor learning motivation. Most learning motivation is influenced by extrinsic factors such as the environment and the atmosphere around it. therefore there needs to be various efforts to motivate adolescents as millennial communities whose conditions are still vulnerable and have a lot to learn. One of them can be through related research, such as this article which indeed reviews the phenomenon. At least offer one alternative, namely bibliotherapy in increasing adolescent learning motivation. This article describes the findings in the field that bibliotherapy can increase adolescent learning motivation, through the stages of identification, selection, presentation and follow-up. The setting of data collection conducted through observation, interviews and documentation is one of the Community Reading Gardens in Yogykarta, namely the Nologaten Smart Cakruk. By involving five informants. Starting from the coaches and teenagers who often interact with Smart Cakruk TBM.